The Obesity-associated Risk in Open and Endovascular Repair of Abdominal Aortic Aneurysm - Radak, Djordje; Tanaskovic, Slobodan; Neskovic, Mihailo (Current Pharmaceutical Design, 2019)
The rising pandemic of obesity in modern society should direct attention to a more comprehensive approach to abdominal aortic aneurysm (AAA) treatment in the affected population. Although overweight patients are considered prone to increased surgical risk, studies on the subject did not confirm or specify the risks well enough. Associated comorbidities inevitably lead to a selection bias leaning towards endovascular abdominal aortic repair (EVAR), as a less invasive treatment option, which makes it hard to single out obesity as an independent risk factor. The increased technical difficulty often results in prolonged procedure times and increased blood loss. Several smaller studies and two analyses of national registries, including 7935 patients, highlighted the advantages of EVAR over open repair (OR) of abdominal aortic aneurysm, especially in morbidly obese population (relative risk reduction up to 47%). On the other hand, two other studies with 1374 patients combined, concluded that EVAR might not have an advantage over OR in obese patients (P = 0.52). Obesity is an established risk factor for wound infection after both EVAR and OR, which is associated with longer length of stay, subsequent major operations, and a higher rate of graft failure. Percutaneous EVAR technique could present a promising solution to reducing this complication. EVAR seems like a more feasible treatment option than OR for obese patients with AAA, due to lower overall morbidity and mortality rates, as well as reduced wound-related complication rates. However, there is a clear lack of high-quality evidence on the subject, thus future prospective trials are needed to confirm this advantage.
Keywords: complications